Beverage consumption patterns in a new market economy - Florkowski, Wojciech J. (Economics and Business Review, 2006)
Beverage consumption reflects consumer behavior shaped by social and economic factors. Observations of beverage consumption patterns provide unique insights of interest to many decision-makers, from the marketers and distributors to public health experts. We apply count data modeling technique to data on beverage consumption frequencies and show the importance of selecting the appropriate model. The models are estimated using survey data collected from more than 2,000 households in Bulgaria. Results from nested and non-nested tests and the ability to predict zero observations suggested that the zero-inflated Poisson with heterogeneity and negative binomial models performed best. Only results of these models are discussed leading to the overall conclusion that age, employment, education and income are the core characteristics of each beverage consuming group, while gender and household characteristics such as the number of adults in the family or the presence of children together with the religion and the geographical location helped to fine tune the profile of beverage consumers. (original abstract)